Factors That Influence Students' Ability To Solve Mathematics Story Problems - Ichdar Domu; Navel Oktaviandy Mangelep (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to examine the factors that influence the ability of class IX junior high school students in Kotamobagu City, North Sulawesi Province, Indonesia, to solve story problems, both theoretical and applied. A total of two hundred and four students in the 2023/2024 academic year were selected using a double-phased cluster sampling technique. The research instrument used in this research was theoretical and applied mathematics story test questions created by researchers. The data obtained were analyzed using path analysis. The results of the analysis show that solving theoretical and applied mathematics story problems shows the same tendency, which is influenced both directly by mathematical numerical and verbal abilities and indirectly by the ability to create mathematical models. From these results, teachers must strive to improve numerical and verbal mathematical abilities because these two abilities, directly or indirectly through the ability to create mathematical models together, can improve students' abilities in solving theoretical and applied word problems.